Monitoring Dan Evaluasi Jalan Raya Rawan Longsor Di Kelurahan Tanah Baru Kecamatan Beji Depok Dan Upaya Penanganannya - Achmad Nadjam; Budi Damianto (Politeknik Negeri Jakarta, 2020)
The Tanah Baru Depok Road is 4.12 km in length consisting of two lanes connecting the Jakarta-Depok route. Current conditions with a road width of 5.2m during the rainy season on the right side of the new dirt road, there are certain parts of the STA, there are certain road conditions that are cracked and landslides. rainy season. The purpose of this research is to conduct monitoring and evaluation of the handling that has been done on the highway, as well as providing these results to make planning for the prevention of landslide prone roads. Stages of methods to be carried out during monitoring are identification of landslide hazard locations (not / moderate / already handled), identification of causes of landslides, identification of consequences, morphological analysis, geology, hydrology, and land use. Whereas in the evaluation stage is the analysis of the handling that has been done and the determination of new treatments. The results of monitoring and evaluation are there are 5 locations on STA Km 3 + 240 and STA Km 3 + 650 landslides, STA Km 1 + 970 and STA Km 2 + 450 potential landslides, STA Km 3 + 840 have dangerous roadside because there is no road divider. Countermeasures for landslide areas are carried out by installing a retaining construction on the right side of the road that intersects the river in the form of a cantilever wall. +840 mounted guardrail to prevent vehicles from entering the river bank..